The Functionalist Approach to Translation and its Application to Translation Management - Isaac Boaheng (Journal of Mother-Tongue Biblical Hermeneutics and Theology)
This research explored the application of the functionalist approach to translation management. The functionalist approach, which emphasizes the purpose and function of a translation within its target context, provided valuable insights for managing translation processes effectively. The research employed a literature-based approach to examine existing literature on the functionalist approach and to examine how its principles can be integrated into translation management practices. The findings highlight how focusing on the functional needs of the target audience and context enhances the efficiency and quality of translation projects. This research contributes to a deeper understanding of how functionalist theories can inform and improve translation management strategies.